IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI KELAS IV SEKOLAH DASAR - Asih, Murni; Wawan Setiawardani; Dadang Suhada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Numeracy literacy can be interpreted as the ability to reason or understand mathematical statements, symbols. The purpose of this study is to find out whether the problem-based learning model is able to improve students' numeracy literacy skills, to find out student activities in learning in improving students' numeracy literacy skills. This research is included in the classroom action research carried out in 3 cycles with the focus of the research being 47 grade IV students at UPTD SDN 4 Krangkeng. Data collection by observation, test and interview techniques. Meanwhile, the data analysis technique is by comparing test results and observations. From the results of the study, it can be concluded that using a problem-based learning model can improve students' numeracy literacy skills in mathematics subjects with stacked division materials. This can be seen from the results of the learning completeness test, which was initially only 30%. In the first cycle, there was an increase to 40% with a total of 19 students who completed. Cycle II increased to 66% with a total of 40 students who completed and in the third cycle increased by 85% with a total of 19 students who completed. Meanwhile, in student learning activities, which was originally 65% in cycle I, and increased by 77.5% in cycle II and increased even more in cycle III by 85%. Based on these results, it can be said that classroom action research with the implementation of a problem-based learning model in the subject of mathematics and stacked division materials in grade IV UPTD SDN 4 Krangkeng is able to improve students' numeracy literacy skills.